(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
This study aimed to investigate the role of Big Data in forecasting corporate bankruptcy and that is through a field analysis in the Saudi business environment, to test that relationship. The study found: that Big Data is a recently used variable in the business context and has multiple accounting effects and benefits. Among the benefits is forecasting and disclosing corporate financial failures and bankruptcies, which is based on three main elements for reporting and disclosing that, these elements are the firms’ internal control system, the external auditing, and financial analysts’ forecasts. The study recommends: Since the greatest risk of Big Data is the slow adaptation of accountants and auditors to these technologies, which have become a reality that most firms seek for management and competitive purposes, accounting skills of accountants must be developed, and to take advantage of the full potential of business intelligence, to deal with the large amount of available data and Big Data applications.